(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
This study examines the application of Management Information System as a predictor of Principals’ administrative effectiveness in secondary schools in Anambra State. Seven research questions guided the study and seven hypotheses were tested at 0.05 level of significance. The correlational survey research design was adopted for the study. All the population of 267 principals of public secondary schools in Anambra State were used for the study. Two questionnaires titled “Management Information Sysem Application Questionnaire (MISAQ) and the Principals’ Administrative Effectiveness Questionnaire (PAEQ) were used to collect data for the study. The instruments were validated by two experts from the Department of Educational Management and Policy and one expert from the Department of Educational Foundation (Measurement and Evaluation) all in the Faculty of Education, Nnamdi Azikiwe University. Internal consistency of the instruments were determined using Cronbach’s Alpha method and coefficients of 0.87 was obtained for MISAQ while 0.81, 0.79, 0.83, 0.85, 0.77, and 0.82 for the six clusters of PAEQ with overall coefficient of 0.81. Data collected for the study were analyzed using regression analysis. P-value was used to determine the significance of prediction at 0.05 significant level. The result among others revealed that MIS application is a moderate predictor of principals’ staff and students’ personnel administration in secondary schools in Anambra State, MIS application is a moderate predictor of school principals’ facilities management in secondary schools in Anambra State. Based on the findings, it was recommended among others that Anambra State Ministry of Education should prioritize equipping secondary schools in Anambra State with robust Management Information Systems (MIS), including sufficient hardware, software, and internet access. It should also establish structured training programmes to build principals’ capacity to leverage MIS for effective administrative decision-making and school management, Post Primary School Service Commission (PPSSC) should integrate MIS competency into principals’ professional development and appraisal, offering workshops and continuous training for effective use in staff, student, and resource management.